Violent subjects and rhetorical cartography in the age of the terror wars - Hayes, Heather Ashley (Rhetoric, politics and society, 2016)
"This work examines violence in the age of the terror wars with an eye toward the technologies of governance that create, facilitate, and circulate that violence. In performing a rhetorical cartography that explores the rise of the US armed drone program as well as moments of resistive violence that occurred during the Arab Spring directed at generating a counter-hegemony by Muslim populations, the author argues that the problem of the global terror wars is best addressed by a rhetorical understanding of the ways that governments, as well as individual subjects, turn to violence as a response to, or product of, the post September 11th terror society. When political examinations of terrorism are facilitated through understandings of discourse, Hayes argues, clearer maps emerge of how violence functions to offer mechanisms by which governing bodies, and their subjects, evaluate the success or failure of the "War on Terror." This book will be of interest to public policymakers and informed general readers as well as students and scholars in the fields of rhetoric, political theory, critical geography, US foreign relations/policy, war and peace studies, and cultural studies"--Page [4] of cover